Transmission of Cryptosporidium Species Among Human and Animal Local Contact Networks in Sub-Saharan Africa: A Multicountry Study. (9th March 2020) - Krumkamp, Ralf; Aldrich, Cassandra; Maiga-Ascofare, Oumou; Mbwana, Joyce; Rakotozandrindrainy, Njari; Borrmann, Steffen; Caccio, Simone M; Rakotozandrindrainy, Raphael; Adegnika, Ayola Akim; Lusingu, John P A; Amuasi, John; May, Jürgen; et al.
Abstract: Background: Cryptosporidiosis has been identified as one of the major causes of diarrhea and diarrhea-associated deaths in young children in sub-Saharan Africa. This study traces back Cryptosporidium- positive children to their human and animal contacts to identify transmission networks. Methods: Stool samples were collected from children < 5 years of age with diarrhea in Gabon, Ghana, Madagascar, and Tanzania. Cryptosporidium- positive and -negative initial cases (ICs) were followed to the community, where stool samples from households, neighbors, and animal contacts were obtained. Samples were screened for Cryptosporidium species by immunochromatographic tests and by sequencing the 18S ribosomal RNA gene and further subtyped at the 60 kDa glycoprotein gene ( gp60 ). Transmission clusters were identified and risk ratios (RRs) calculated. Results: Among 1363 pediatric ICs, 184 (13%) were diagnosed with Cryptosporidium species. One hundred eight contact networks were sampled from Cryptosporidium- positive and 68 from negative ICs. Identical gp60 subtypes were detected among 2 or more contacts in 39 (36%) of the networks from positive ICs and in 1 contact (1%) from negative ICs. In comparison to Cryptosporidium -negative ICs, positive ICs had an increased risk of having Cryptosporidium -positive household members (RR, 3.6 [95% confidence interval CI, 1.7–7.5]) or positive neighboring children (RR, 2.9 [95% CI, 1.6–5.1]), but no increased risk of having positive animals (RR, 1.2 [95% CI, .8–1.9]) in their contact network. Conclusions: Cryptosporidiosis in rural sub-Saharan Africa is characterized by infection clusters among human contacts, to which zoonotic transmission appears to contribute only marginally. Abstract : A contact network analysis in 4 countries of sub-Saharan Africa revealed Cryptosporidium neighborhood clusters in rural communities with human-to-human transmission being the predominant transmission route, while zoonotic transmission appears to contribute only marginally.